Penggunaan Artificial Intelligence Dalam Pengembangan Perangkat Pembelajaran Pai Di SMP Negeri 22 Kota Surabaya - Fahmi Ayatillah, M. Ishom; Luqna Hunaida, Wiwin; Muqit, Abd. (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2024)
This study aims to explore the use of Artificial Intelligence (AI) in the development of Islamic Religious Education (PAI) learning tools at SMP Negeri 22 Surabaya City. The approach used is qualitative with field research method, involving in-depth interviews with PAI teachers to understand the experiences and challenges in implementing AI-based technology. The results showed that AI has great potential to improve the efficiency and quality of learning by providing adaptive and customized teaching tools, including teaching modules, teaching materials, and interactive media. However, the implementation of AI still faces challenges, especially teachers limited digital literacy. To overcome this obstacle, this study recommends structured training for teachers as well as the establishment of a support community to share knowledge related to AI implementation. This study concludes that the integration of AI in PAI can play an important role in improving the quality of education in the digital era.